Gender and Human Rights Challenges: An Analysis of the Iranian Government's Political Influence on Family Law - Sulung Najmawati Zakiyya (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2024)
From the early 20th century to the present day, Iran has undergone various political changes that have affected the regulation of family law in the country. From the codification of civil law in 1928-1935 to the Islamic Revolution of 1979, various political regimes have influenced the interpretation and implementation of family law, which in turn affected the status and rights of women and society as a whole. This article attempts to analyze the evolution of family law in Iran, focusing on the impact of politics on gender equality and human rights. It also discusses the challenges and controversies that have arisen in relation to the reinterpretation of Islamic family law following the Islamic Revolution. Although some reforms aimed to improve women's protection, in many cases, new interpretations of family law have reinforced patriarchal norms and restricted women's freedom in various aspects of life. Through a literature review and policy analysis, this article presents significant changes in family law regulations, including restrictions on polygamy, divorce proceedings, and inheritance rights, and how they affect women's rights in Iran. The results show that political influences on family law in Iran have had a significant impact in the context of gender equality and human rights. From the codification of civil law to new interpretations after the Islamic Revolution, various political regimes have shaped legal frameworks that affect the status and rights of women and society as a whole. While some reforms have aimed to improve women's protection, in many cases, reinterpretations of Islamic family law have reinforced patriarchal norms and restricted women's freedoms. Therefore, an in-depth understanding of the relationship between politics and family law is essential to strive for more inclusive and progressive changes in order to achieve gender equality and human rights in Iran.